Multiliteracy-Based Islamic Education for Students For 21st Century Competency Strengthening - Mohamad Munawar; Ahmad Setio Widodo; Husna Imro'athush Sholihah (JURNAL PEDAGOGY, 2026)
This study aims to analyze multiliteracy-based Islamic education as a strategy to strengthen the competence of students in the 21st century. This study is motivated by technological and information developments that require students to have digital literacy, information literacy, media literacy, visual literacy, and cultural literacy skills in order to be able to deal with social, academic, and world of work changes adaptively. This research uses a qualitative approach with a case study method at STAI Muhammadiyah Blora, through data collection techniques in the form of observation, interviews, and documentation studies. The results of the study show that multiliteracy-based Islamic education can improve students' ability to sort information, think critically, understand Islamic teachings more deeply, use technology wisely, and develop religious, creative, innovative, and responsible character. However, its implementation still faces challenges in the form of low understanding of educators and students on the concept of multiliteracy, limited resources, and the need for a curriculum that is more relevant to the needs of the 21st century. Therefore, multiliteracy-based Islamic education needs to be supported through the development of innovative learning methods, strengthening lecturer competencies, utilizing information technology, and collaboration between educational institutions, the government, parents, and the community. Thus, this approach can be a model for the development of Islamic education that is academic, practical, and contextual in forming students who are critical, adaptive, moral, and ready to contribute positively to society in the digital era.